Enhancing personal development of learners with disabilities through pedagogical practices: Teachers’ perspectives in the High Glen district, Zimbabwe - Loveness Dube; Liana Musekiwa; James Maizere (International Journal of Studies in Inclusive Education)
One of the most critical tasks of special and inclusive education in the current context of education system reform is the social and pedagogical support of children with disabilities to enhance personal development. The personal development of learners with disabilities is a critical area of focus in contemporary education. The study explored the pedagogical practices used to improve the personal development of learners with disabilities in inclusive classes. It adopted an interpretive paradigm, a qualitative research approach, and a case study research design. Fourteen participants were purposively selected from the population: head teachers, teachers, and learners with disabilities of two schools in the High Glen district, Zimbabwe. This study collected data from semi-structured interviews, observations, and focus group discussions. Data were analysed through thematic analysis. Results indicated that positive reinforcement, individualised instructions, creating relationships, engaging learners in different roles and activities, promoting learner-learner, and using role models could be considered pedagogical practices to enhance the personal development of learners with disabilities. The results also found the challenges in implementing these practices, such as the lack of teachers’ frustrations and government and parental support. This study recommended that all stakeholders, including the government and the parents, provide support systems for learners with disabilities.